2013
DOI: 10.1038/hdy.2013.71
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the bull’s eye: agents and targets of selection vary among geographically disparate cyanogenesis clines in white clover (Trifolium repens L.)

Abstract: Searching for the bull's eye: agents and targets of selection vary among geographically disparate cyanogenesis clines in white clover (Trifolium repens L.) NJ Kooyers 1 and KM OlsenThe recurrent evolution of adaptive clines within a species can be used to elucidate the selective factors and genetic responses that underlie adaptation. White clover is polymorphic for cyanogenesis (HCN release with tissue damage), and climateassociated cyanogenesis clines have evolved throughout the native and introduced species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 57 publications
6
64
1
Order By: Relevance
“…Cyanogenic clover plants are differentially protected against a variety of small generalist herbivores (reviewed in Kooyers et al ., ). At the same time, acyanogenic plants predominate at higher latitudes and elevations, and climate‐associated cyanogenesis clines have evolved in native and naturalized populations worldwide (e.g., Daday, ,b, ; Kooyers & Olsen, , ; Thompson et al ., ). Glasshouse experiments indicate that there are energetic costs associated with the production of the cyanogenic components (Kakes, ; Kooyers et al ., ); acyanogenic plants may therefore have a competitive advantage in cooler climates if fewer herbivores are present in these locations.…”
Section: Discussionmentioning
confidence: 99%
“…Cyanogenic clover plants are differentially protected against a variety of small generalist herbivores (reviewed in Kooyers et al ., ). At the same time, acyanogenic plants predominate at higher latitudes and elevations, and climate‐associated cyanogenesis clines have evolved in native and naturalized populations worldwide (e.g., Daday, ,b, ; Kooyers & Olsen, , ; Thompson et al ., ). Glasshouse experiments indicate that there are energetic costs associated with the production of the cyanogenic components (Kakes, ; Kooyers et al ., ); acyanogenic plants may therefore have a competitive advantage in cooler climates if fewer herbivores are present in these locations.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, numerous biological studies have detected clinal variation in traits across altitudinal gradients (Barber & Jackson, ; Pitchers, Pool, & Dworkin, ). Recent studies have further suggested that the presence of replicated clines across independent geographical systems can strengthen inferences regarding the “agents and targets” of natural selection (Kooyers & Olsen, ).…”
Section: Introductionmentioning
confidence: 99%
“…; Caradus & Forde ; Majumdar et al . ), as well as in regions where white clover has been introduced and naturalized, such as the central United States (Daday ; Kooyers & Olsen ), New Zealand (Kooyers & Olsen ) and the U.S. Pacific Northwest (Ganders ; Kooyers & Olsen ). For example, in the central United States, we have documented that the frequency of cyanogenic plants steadily decreases over a ~900km latitudinal transect from 86% in southern Louisiana to 11% in northern Wisconsin (Kooyers & Olsen ).…”
Section: Introductionmentioning
confidence: 99%